Kto jest autorką tzw. "Pamiętnika Galicjanki (1914-1917)"? = Who is the author of the so-called "Pamiętnik Galicjanki" (Galician`s diary) "(1914-1917)"? - Jazownik, Maria; Jazownik, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is presentation of research results concerning determination of the author of the diary notes from the period of the First World War published in 2012 under the title "Pamiętnik Galicjanki" (Galician`s Diary) "(1914-1917)". The publisher of the diary - Maciej Dęborog-Bylczyński - recognized that its author is Magdalena Bylczyńska (1887-1966), a music teacher from Lviv, and the co-author is her stepmother, Rozalia of the Holmanns Webersfeld (1847-1936).
Keywords: Polish diary keeping; First World War; Eastern Galicia; Bylczyńska, Magdalena (1887-1966); Webersfeld, Rozalia (1847-1936); Obertyńska, Maria Kamilla (1861-1956); I wojna światowa (1914-1918); Galicja; pamiętnikarstwo polskie